Participation in leisure activities to maintain cognitive health: Perceived educational needs of older adults with stroke. Issue 1 (2nd January 2019) - Poulin, Valérie; Carbonneau, Hélène; Provencher, Véronique; Rochette, Annie; Giroux, Dominique; Verreault, Cynthia; Turcotte, Samantha
Abstract : Leisure participation may promote cognitive health in older adults who have had a stroke. It is important to provide them with the appropriate tools and resources in order to enable them to engage in these activities. The objective of this study is to identify the educational needs of older adults who have had a stroke in order to support their participation in leisure activities that promote cognitive health. Convergent mixed-methods design was used, with the emphasis on qualitative data, and involving semi-structured interviews with 20 people aged 60 or older who have had a stroke and live at home. The results showed that the profile of participation in leisure and the level of met and unmet needs vary among participants. One of the main needs concerns long-term follow-up and support to pursue personal goals. Preferences include tools and resources promoting active involvement, interactions, and opportunities for choice and control. These results may guide the development of a leisure education program for this population at high risk of cognitive decline.